The Effect of Training and Work Discipline on Employee Performance in The Fire Fighting and Rescue Service - Yhonanda Harsono; Tasya Pratiwi; Linda Afriani (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2023)
The purpose of this study is to determine the effect of training and work discipline on employee performance in the South Jakarta Administrative City Fire and Rescue Service Tribe both partially and simultaneously. The method used in this study is associative quantitative. This study took a sample of 82 respondents. Partial hypothesis test of the Training variable (X1) obtained a calculated value of > ttabel or (15.564 > 1.99006) thus H01 rejected Ha1 is accepted it is also reinforced by the value of ρ value < Sig. 0.05 or (0.000 < 0.05). Partial hypothesis test of labor discipline variables (X2) obtained thitung > ttabel or (21.222 > 1.99006) thus H02 is rejected and Ha2 is accepted as well reinforced by the value of ρ value < Sig. 0.05 or (0.000 < 0.05). This means that there is a significant influence between Work Discipline on Employee Performance. The hypothesis test simultaneously obtained the Fhitung value of > Ftabel or (295.638 > 3.11) it was also reinforced by ρ value < Sig. 0.05 or (0.000 < 0.05). Thus H03 is rejected and Ha3 is accepted. This means that there is a simultaneous significant influence between Training and Work Discipline on Employee Performance. The coefficient of multiple determinations obtained an R-square value of 0.882, so it can be concluded that the training variable (X1) and work discipline (X2) affects the employee performance variable (Y) has a very strong relationship of 88.2 while the remaining 11.8% is influenced by other factors that were not studied.